Zinc-Catalyzed Carbon Dioxide Based Biodegradable Polycarbonate Synthesis - Liu, Yuyu; Yang, Shanxiu; Li, Pan; Wang, Hao; Cui, Xinjiang; Qian, Bo; Shi, Feng (Synthesis, 2025)
Carbon dioxide based degradable polycarbonate can be obtained through the copolymerization reaction of carbon dioxide with epoxide in the presence of a catalyst. This polymer has attracted much attention in recent years owing to its environmentally friendly and sustainable characteristics, and excellent material properties. Due to its unique properties, CO2-based polycarbonate has a wide range of applications in many fields such as electronic and electrical parts, automotive parts, medical devices, aerospace equipment, power electronic equipment, and radiation protection products. Therefore, numerous catalytic systems have been explored for the CO2/epoxide copolymerization process, in which zinc catalyst has the longest history and the greatest variety. In this short review, the significant advances in zinc catalysts for the copolymerization transformation of CO2 with epoxide are demonstrated, covering both heterogeneous and homogeneous catalysts. Moreover, both benefits and drawbacks of zinc catalytic system are described, and the outlook for large-scale industrial applicati ons in the future is also represented.1 Introduction2 Heterogeneous Zinc Catalysts3 Homogeneous Zinc Catalysts4 Overview of Heterogeneous and Homogeneous Zinc Catalysts5 Conclusion
Keywords: zinc catalyst; carbon dioxide; epoxide; copolymerization; biodegradable polycarbonate synthesis